Performance comparison of jet pumps with rectangular and circular tapered channels for a loop-structured traveling-wave thermoacoustic engine. (15th June 2015) - Tang, K.; Feng, Y.; Jin, S.H.; Jin, T.; Li, M.
Highlights: Three evaluating parameters are proposed to characterize performance of a jet pump. The performances of jet pumps with rectangular and circular tapered channels are compared. Thickness-to-diameter ratio can change the magnitude and direction of the time-averaged pressure drop of jet pump. A jet pump with rounded circular tapered channel can work more efficiently. Abstract: Gedeon streaming can considerably deteriorate the thermal efficiency of a traveling-wave thermoacoustic engine employing a loop configuration. Introducing a jet pump into the loop configuration is one of the effective ways to suppress Gedeon streaming. This paper focuses on the performance comparison between the jet pumps with rectangular and circular tapered channels, by numerically simulating and analyzing the time-averaged pressure drop induced by the jet pumps. Three parameters, i.e., the coefficient of time-averaged resistance, the coefficient of overall resistance, and the coefficient of effectiveness, are proposed to evaluate the performance of a jet pump. The emphasis is put on the effects of cross-sectional shape, thickness-to-diameter ratio, and rounding radius of the tapered channels. In absence of rounding the edge of the tapered channel, the jet pump with a rectangular tapered channel is more efficient to produce the time-averaged pressure drop at a large thickness-to-diameter ratio, while the jet pump with a circular tapered channel is more efficient at a small thickness-to-diameter ratio. However, it should be noted that the directions of the induced time-averaged pressure drops in these two cases are opposite. Rounding the edge of the small opening of the tapered channel can effectively improve jet pump's performance. Upon rounding, the jet pump with a circular tapered channel can produce a higher time-averaged pressure drop and work more efficiently than the one with a rectangular tapered channel.